2019
DOI: 10.32820/2074-8922-2019-65-147-155
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Evaluation of the Potential of Infographics as Powerful Tools in English Language Teaching

Hanna Korniush

Abstract: The present article sheds light on the opportunities that using infographics in the ELT classroom offers. The author of the paper dwells upon the definition of the term "infographics" and explains why an infographic is an effective and powerful medium of instruction in the contexts of blended learning and edutainment, which are currently gaining more and more popularity. Particular attention is paid to the advantages of incorporating infographics in the educational process, with special emphasis being placed o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…Moreover, Khan (2021) confirmed that infographics had a positive impact on building EFL learners' vocabulary and motivating them through interesting and colorful visual descriptions. In consideration of all these points, it is possible to disclose that infographics are versatile with their usefulness and promising contributions to language learning and teaching that can cover the instruction of grammar and vocabulary, and improving language skills (Dipa, Utami, & Santosa, 2022;Korniush, 2019).…”
Section: Qualitative Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, Khan (2021) confirmed that infographics had a positive impact on building EFL learners' vocabulary and motivating them through interesting and colorful visual descriptions. In consideration of all these points, it is possible to disclose that infographics are versatile with their usefulness and promising contributions to language learning and teaching that can cover the instruction of grammar and vocabulary, and improving language skills (Dipa, Utami, & Santosa, 2022;Korniush, 2019).…”
Section: Qualitative Resultsmentioning
confidence: 99%
“…Thus, technologically enhanced visuals are effective to teach both grammar and vocabulary in language classrooms (Adriana, 2017). It was also implicated that infographics yield important speed advantages when designed for improving the literary and language skills of learners of English (Dipa, Utami, & Santosa, 2022;Korniush, 2019). Fadhil (2018) found that infographics helped learners to remember the related materials easily.…”
Section: Review Of Literaturementioning
confidence: 99%